Yacht type and crew-specific differences in anthropometric, aerobic capacity, and muscle strength parameters among international Olympic class sailors - Bojsen-Moeller, J.; Larsson, B.; Magnusson, S. P.; Aagaard, P. (Journal of Sports Sciences, 2007)
Physical fitness and muscular strength are important performance factors for Olympic class sailors, but the physical demands vary greatly between yacht classes, and limited information is available regarding the physical demands for the different crew positions. In the present paper, strength and aerobic capacity data from elite Olympic sailors are presented and compared with previous findings. Furthermore, a system for classification of Olympic class sailors is suggested. Peak aerobic capacity (peak oxygen uptake, O2peak) and maximal isometric and isokinetic muscle strength of the knee extensors and flexors were assessed, together with the hamstring/quadriceps strength ratio (H/Q ratio). Peak aerobic capacity (ml O2 · min-1 · kg-2/3) was as follows: males - static hikers (n = 5) 215, s = 7; dynamic hikers (n = 8) 252, s = 17; trapezing helmsmen (n = 6) 234, s = 15; trapezing crew (n = 10) 239, s = 16; females - dynamic hikers (n = 6) 194, s = 16; trapezing crew (n = 2) 200, s = 13. Strength data for hikers, presented as peak moments (normalized to body weight) obtained during eccentric, isometric, and concentric contraction (Nm · kg-1) respectively were as follows: males - quadriceps: 3.66 (s = 0.68), 3.97 (s = 0.66), 1.82 (s = 0.34); hamstrings: 1.93 (s = 0.22), 1.38 (s = 0.41), 1.05 (s = 0.21); females - quadriceps: 3.84 (s = 0.71), 3.81 (s = 0.58), 1.60 (s = 0.28); hamstrings: 1.75 (s = 0.23), 1.10 (s = 0.16), 0.84 (s = 0.13). The peak moment based H/Q ratios for slow eccentric and concentric contractions were 0.42 (s = 0.11) and 0.39 (s = 0.04) for males and 0.43 (s = 0.06) and 0.39 (s = 0.04) for females respectively. Elite Olympic class sailors demonstrated high O2peak values comparable to those observed in other non-endurance sports. The strength data revealed very high quadriceps strength for hikers, which is likely a result of the high muscle forces encountered during sailing, and a low H/Q ratio. To ensure optimal knee joint stabilization during sailing and other training activities, it is suggested that hikers should counter this strength imbalance by performing additional strength training for the hamstrings muscle group.